Linear Ion Source를 이용한 Anode Voltage 변화에 따른 DLC 박막특성 - 김왕렬(Wang Ryeol Kim); 정우창(Uoo Chang Jung); 조형호(Hyung Ho Jo); 박민석(Min Suk Park); 정원섭(Won Sub Chung) (Biuletyn Uniejowski, 2009)
Diamond-like carbon(DLC) films were deposited by linear ion source(LIS)-physical vapor deposition method changing the anode voltages from 800 V to 1800 V, and characteristics of the films were investigated using residual stress tester, nano-indentation, micro raman spectroscopy, scratch tester and Field Emission Scanning Electron Microscope(FE-SEM). The results showed that the residual stress and hardness increased with increasing the ion energy up to anode voltage of 1400 V. It was also found that the content of $SP^3$ carbon increased with increasing the anode voltage $SP^3/SP^2$ ratio through investigation of $SP^3/SP^2$ ratio by the micro-raman analysis. From these results, it can be concluded that the physical properties of DLC films such as residual stress and hardness are increased with increasing the anode voltage. These results can be explained that 3-dimensional cross-links between carbon atoms and Dangling bond are enhanced and the internal compressive stress also increased with increasing the anode voltage. The optimal anode voltage is considered to be around 1400 V in these experimental conditions.